Evaluation of a Computer-Tailored Osteoporosis Prevention Intervention in Young Women. - Lein, Donald H.; Clark, Diane; Turner, Lori W.; Kohler, Connie L.; Snyder, Scott; Morgan, Sarah L.; Schoenberger, Yu-Mei M. (American Journal of Health Education)
The purpose of this study was to evaluate the effectiveness of a theory-based computer-tailored osteoporosis prevention program on calcium and vitamin D intake and osteoporosis health beliefs in young women. Additionally, this study tested whether adding bone density testing to the intervention improved the outcomes. Methods One hundred (n = 100) women aged 19 to 25 years were randomly assigned to one of 2 groups. One group (n = 50) received the computer-tailored program with brief counseling and the second group (n = 50) received the same intervention plus bone density testing of the heel (quantitative ultrasound [QUS]) feedback. Results Participants within both groups statistically significantly increased calcium and vitamin D intake from baseline to 1 month after the interventions. Both groups also experienced statistically significant decreases in perceived barriers to obtaining adequate vitamin D intake. Discussion The theory-based computer-tailored osteoporosis prevention program resulted in significant improvements in osteoporosis beliefs and calcium and vitamin D intakes. The bone density test did not improve results. Translation to Health Education Practice Though future research is needed, this preliminary study holds promise for health education practice to use theory to plan osteoprotective computer programs for young women.